Unveiling The Odyssey : A Feminist Comparative Study of Three English Translations Concentrating on the Maids - Masalin, Marika (My University, 2024)
This bachelor’s thesis examines three English translations of The Odyssey, focusing on the portrayal of the maids that appear in the poem. Specifically, the translations by Fitzgerald (1961), Fagles (1996), and Wilson (2017) are analysed to compare their treatment of female characters and assess whether Wilson's translation can be considered feminist. The study adopts a comparative approach, drawing examples from Books 16, 18, 19, 20, and 22 of the poem. These examples are analysed using a framework informed by Mills' (2008) categorisation of overtly sexist language and feminist translation theory proposed by von Flotow (1991). The analysis reveals differences between Wilson's translation and the earlier two. Unlike Fitzgerald and Fagles, Wilson's translation avoids the use of sexist insult terms such as slut. It also uses a different approach when it comes to translating words associated with domestic servants, especially the maids. While Wilson's translation does not explicitly incorporate feminist translation strategies, its avoidance of overtly sexist language suggests a non-sexist approach to translation. In conclusion, this thesis highlights the ways in which translations of classical texts can reflect and perpetuate gender biases. By examining specific examples and applying theoretical frameworks, it contributes to discussions about the role of translation in shaping interpretations of literary works.
Keywords: feminist translation, feminism, sexism